Selective inhibition of EZH2 and EZH1 enzymatic activity by a small molecule suppresses MLL-rearranged leukemia - Xu, Bowen (Blood, 2015)
Enhancer of zeste homolog 2 (EZH2) and related EZH1 control gene expression and promote tumorigenesis via methylating histone H3 at lysine 27 (H3K27). These methyltransferases are ideal therapeutic targets due to their frequent hyperactive mutations and overexpression found in cancer, including hematopoietic malignancies. Here, we characterized a set of small molecules that allow pharmacologic manipulation of EZH2 and EZH1, which include UNC1999, a selective inhibitor of both enzymes, and UNC2400, an inactive analog compound useful for assessment of off-target effect. UNC1999 suppresses global H3K27 trimethylation/dimethylation (H3K27me3/2) and inhibits growth of mixed lineage leukemia (MLL)–rearranged leukemia cells. UNC1999-induced transcriptome alterations overlap those following knockdown of embryonic ectoderm development, a common cofactor of EZH2 and EZH1, demonstrating UNC1999's on-target inhibition. Mechanistically, UNC1999 preferentially affects distal regulatory elements such as enhancers, leading to derepression of polycomb targets including Cdkn2a. Gene derepression correlates with a decrease in H3K27me3 and concurrent gain in H3K27 acetylation. UNC2400 does not induce such effects. Oral administration of UNC1999 prolongs survival of a well-defined murine leukemia model bearing MLL-AF9. Collectively, our study provides the detailed profiling for a set of chemicals to manipulate EZH2 and EZH1 and establishes specific enzymatic inhibition of polycomb repressive complex 2 (PRC2)–EZH2 and PRC2-EZH1 by small-molecule compounds as a novel therapeutics for MLL-rearranged leukemia.